1971
DOI: 10.1002/ejsp.2420010202
|View full text |Cite
|
Sign up to set email alerts
|

Social categorization and intergroup behaviour

Abstract: RPsumPLe but des ttudes Ctait de determiner les effets de la catkgorisation sociale sur le comportement inter-groupe, quand, dans la situation inter-group, on ne pouvait incriminer ni des calculs d'intCr&t individuel ni des attitudes hostiles prtexistantes en ce qui wncerne le comportement discriminatoire vis-A-vis d'un groupe exterieur. Ces conditions ttaient remplies dans le plan ex-p6rimental. L a premiere drie d'exptriences a demonstrk que les sujets favorisaient leur propre groupe dans la distribution de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
2,636
9
116

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,308 publications
(2,823 citation statements)
references
References 13 publications
62
2,636
9
116
Order By: Relevance
“…This perspective suggests that social identities serve as anxiety-buffering mechanisms because positive group-based self-esteem appeases existential concerns. Arndt, Greenberg, Schimel, Pyszczynski, and Solomon's (2002) It is worth noting that we employed the minimal group paradigm (Tajfel et al, 1971) in the classification of partici- (1996), the results in the present study support the assertion that minimal ingroups could serve the same worldview defense functions as salient ingroups. Furthermore, the fact that we used minimal groups has another implication for research on self-ingroup overlap.…”
Section: Response Time Analysissupporting
confidence: 78%
See 2 more Smart Citations
“…This perspective suggests that social identities serve as anxiety-buffering mechanisms because positive group-based self-esteem appeases existential concerns. Arndt, Greenberg, Schimel, Pyszczynski, and Solomon's (2002) It is worth noting that we employed the minimal group paradigm (Tajfel et al, 1971) in the classification of partici- (1996), the results in the present study support the assertion that minimal ingroups could serve the same worldview defense functions as salient ingroups. Furthermore, the fact that we used minimal groups has another implication for research on self-ingroup overlap.…”
Section: Response Time Analysissupporting
confidence: 78%
“…We then used the typical minimal group procedure to make artificial laboratory groups (Tajfel et al, 1971). By using the minimal groups, we avoided potential confounds of participants' prior knowledge in the trait evaluation task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research in psychology has examined, on the one hand, the effects of authority on obedience and norm compliance (Milgram, 1963), in-group/out-group effects on moral behavior (Tajfel et al, 1971), and the consequences of emotional cues on people's normative judgments (Schnall et al, 2008;Wheatley and Haidt, 2005). On the other hand, research studies on humans and nonhuman primates have shown that both species tend to adjust their behavior and beliefs toward others in their social circles (Cialdini and Goldstein, 2004;Whiten, Horner and de Waal, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Research using both the minimal group paradigm (Tajfel, 1970;Tajfel, Billig, Bundy, & Flament, 1971) and the illusory correlation paradigm (Hamilton & Gifford, 1976) demonstrated differentiation between groups for which there was no informational basis. Participants in those studies were given information about groups that they used to make group judgments.…”
Section: Theoretical Context: Implications Of Stigs For Stereotype Fomentioning
confidence: 99%